1979
DOI: 10.1017/s1323358000026151
|View full text |Cite|
|
Sign up to set email alerts
|

Position and Polarization of Solar Drift Pair Bursts

Abstract: Reverse drift pairs were first described by Roberts (1958) and later by Ellis (1969) and de la Nòe and Moller-Pedersen (1971). Figure 1 shows a 10-min section of the spectrograph record and the corresponding section of the polarimeter record. The figure contains several reverse drift pairs and illustrates the main features of RDPs, namely: (1) frequency drift rate of about 4 MHz s-1 (i.e. a factor of ~50 faster than Type lis and a factor of ~2 slower than type Ills); (2) drift to higher frequencies (i.e. oppos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

1980
1980
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 4 publications
3
15
1
Order By: Relevance
“…By the way, this feature was accompanied by weak solar activity. All this is consistent with the results of Suzuki and Gary (1979) obtained at a higher frequency. To provide the angular selection of DP component sources in this frequency range, we are going to perform special interferometer measurements in prospect.…”
Section: B) Drift Pair Burstssupporting
confidence: 93%
See 1 more Smart Citation
“…By the way, this feature was accompanied by weak solar activity. All this is consistent with the results of Suzuki and Gary (1979) obtained at a higher frequency. To provide the angular selection of DP component sources in this frequency range, we are going to perform special interferometer measurements in prospect.…”
Section: B) Drift Pair Burstssupporting
confidence: 93%
“…The current state of spectral research of DPs is presented in the recent paper of Stanislavsky et al (2017). However, as for the mapping of DP sources, one can mention only the long-standing paper of Suzuki and Gary (1979). The radio imaging of DPs were carried out at a single frequency (at 43 MHz), and new heliographic observations are very relevant.…”
Section: Datamentioning
confidence: 99%
“…But in this case, the second component, as was correctly noted by Riddle (1974), is to be both decreased in intensity and smoothed, which is not confirmed by observations. Besides that, the heliographic observations (Suzuki and Gary, 1979) show that the place of generation of both components is practically the same. Melrose (1982) proposed the model, in which DPs components are formed because of reflections from duct walls.…”
Section: Discussionmentioning
confidence: 73%
“…Another property of DPs is constant time delay of the second element which equals 1-2 s at all frequencies. Suzuki and Gary (1979) noted that both DP elements had the same sense of polarization but their degree of polarization was different. They also provided the results of radioheliograph data, which showed that source positions were the same for both DP elements and coincided with the Type III source position.…”
Section: Introductionmentioning
confidence: 99%
“…The most enigmatic characteristic of DPBs is that in contrast to other multi-stripe bursts (e.g., type II bursts and zebra patterns), their components are shifted in time rather than in frequency -the second component of a pair looks like a repetition of the first one (although sometimes with a slightly different intensity), while the frequency shift is absent or very small (Ellis 1969;de La Noe & Moller Pedersen 1971;Moller-Pedersen et al 1978;Melrose 1982;Melnik et al 2005). The polarization degree varies from very low to ∼ 50%; the higher-frequency component (i.e., the first component of the pairs with positive frequency drift and the second component of the pairs with negative frequency drift) generally has a higher polarization degree (Suzuki & Gary 1979;Dulk et al 1984). Sometimes, unusual variations of DPBs are observed, such as the so-called hooks and structures with a third component (Ellis 1969;Melnik et al 2005).…”
Section: Introductionmentioning
confidence: 99%